2019
DOI: 10.21834/e-bpj.v4i12.1937
|View full text |Cite
|
Sign up to set email alerts
|

Five Accessibility Challenges in Access Auditing Mosque Designs

Abstract: Grand Mosque is a frequently visited building because it is a place for worshipping God for devoted Muslims and its communal qualities. The lack of access to Mosque creates physical barriers for PwDs and elderly and has discouraged them to join congregational prayers. Mosque accessibility is a prolonged issue that needs to be mitigated. There are five identified access challenges that will be discussed. Revisits mosque’s design intentions and conducting Access Audit at grand mosques for accessibility. Finally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(26 reference statements)
0
1
0
1
Order By: Relevance
“…Šis tyrimas atskleidė, kad asmenys, turintys judėjimo negalią, retai lankosi turistinėse vietose ir beveik niekada nesinaudoja turizmo paslaugomis, nes Lietuvoje apgyvendinimo, maitinimo, kultūros įstaigos, kelionių organizavimo įmonės, viešasis transportas, jų teigimu, yra prieinami tik iš dalies 24 Užsienio mokslinių darbų šaltiniuose galima rasti nemažai universalaus dizaino tyrimų, bet jį reglamentuojančių teisės aktų tyrimų rasta nedaug. Daugiausiai UD teisinę bazę analizuoja Danijos mokslininkai: Grangaard 30 , Kirkeby 31 , Rasmussen 32 ; Malaizijos mokslininkai Said, Samad 33 ir kiti. Nustatyta, kad dauguma užsienio mokslininkų analizuoja asmenų su negalia socialinės integracijos pokyčius, atsiradusius taikant universalaus dizaino principus.…”
Section: Universalaus Dizaino Taikymas Aplinkos Užstatymui: Mokslinių...unclassified
“…Šis tyrimas atskleidė, kad asmenys, turintys judėjimo negalią, retai lankosi turistinėse vietose ir beveik niekada nesinaudoja turizmo paslaugomis, nes Lietuvoje apgyvendinimo, maitinimo, kultūros įstaigos, kelionių organizavimo įmonės, viešasis transportas, jų teigimu, yra prieinami tik iš dalies 24 Užsienio mokslinių darbų šaltiniuose galima rasti nemažai universalaus dizaino tyrimų, bet jį reglamentuojančių teisės aktų tyrimų rasta nedaug. Daugiausiai UD teisinę bazę analizuoja Danijos mokslininkai: Grangaard 30 , Kirkeby 31 , Rasmussen 32 ; Malaizijos mokslininkai Said, Samad 33 ir kiti. Nustatyta, kad dauguma užsienio mokslininkų analizuoja asmenų su negalia socialinės integracijos pokyčius, atsiradusius taikant universalaus dizaino principus.…”
Section: Universalaus Dizaino Taikymas Aplinkos Užstatymui: Mokslinių...unclassified
“…These were the entrances, the wayfinding and path of travel, the prayer hall, the ablution area, and the WCs. They found that some PWDs' accommodations -such as private WCs-were not provided, and while some were provided, they did not comply with standards -as was the case in a steep ramp- [19]. Finally, Mohamad Nazir et al found that most Malaysian mosques' samples (4 out of 5) were unequipped with WC units suitable for PHUWs [20].…”
Section: Pwds' Accessibility At Mosquesmentioning
confidence: 99%